Glanzmann's thrombasthenia with mild von Willebrand's disease. Issue 12 (December 1993) - Nounou, R; Spence, D
Abstract : A Saudi Arabian family is reported in which Glanzmann's thrombasthenia and von Willebrand's disease occurred simultaneously. The daughter presented with menorrhagia and gave a history of gastrointestinal bleeding and a strong family history of bleeding disorder. Full haematological investigations were performed on the propositus, parents, and siblings, including complete blood count, bleeding time, prothrombin time, partial thromboplastin time, factor VIII:C, von Willebrand factor, ristocetin cofactor, platelet aggregometry, platelet glycoprotein Ib and IIb/IIIa and platelet antigen PLT-1 (Coulter Clone). The propositus had Glanzmann's thrombasthenia, both parents had mild von Willebrand's disease and were carriers of Glanzmann's thrombasthenia. Three symptomatic brothers had both Glanzmann's thrombasthenia and von Willebrand's disease; two asymptomatic brothers had von Willebrand's disease only and one had completely normal results. Those family members with both diseases were more severely affected than those with just one disease. In areas where consanguineous marriage is common, such as Saudi Arabia, multiple haemostatic abnormalities may occur, and investigation should not stop with the discovery of a single abnormality. The increased clinical severity of bleeding, including haemarthroses, in those patients having both congenital defects emphasises the importance of von Willebrand factor in glycoprotein Ib-mediated platelet adhesion.